PENERAPAN METODE PERMAINAN KOCOK SUMPIT UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII DI SMPN 1 AIR SALEK - Safitri Ani; Maryamah; Sofyan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low learning motivation of 7th-grade students in the Islamic Religious Education subject at SMPN 1 Air Salek, characterized by a lack of attention, self-confidence, and perceived material relevance, as well as low student learning satisfaction. The study aimed to determine the effect of implementing the "chopstick-shake game" method on enhancing student learning motivation. A quantitative approach was employed using a quasi-experimental design specifically, a Two-Group Pretest-Posttest Design. The sample consisted of 44 students selected via purposive sampling and divided into experimental and control groups. Data were collected using the ARCS learning motivation questionnaire (validated for validity and reliability) and analyzed using normality tests, homogeneity tests, independent t-tests, and N-Gain tests with SPSS version 27 software. The independent sample t-test results showed a significance value of 0.001 (p < 0.05), confirming a significant difference in motivation improvement between the experimental and control groups. The mean learning motivation score in the experimental class rose from 47.00 to 77.29, whereas in the control class, it increased only from 43.73 to 52.43. The N-Gain score for the experimental class was 57.09, indicating a "moderately effective" category. These findings conclude that the chopstick-shake game method is significantly effective in enhancing student learning motivation.